Symmetries and time evolution in discrete phase spaces: a soluble model calculation - Galetti, D. [UNESP]; de Toledo Piza, A. F R (Elsevier, 1995)
Using the flexibility and constructive definition of the Schwinger bases, we developed different mapping procedures to enhance different aspects of the dynamics and of the symmetries of an extended version of the two-level Lipkin model. The classical limits of the dynamics are discussed in connection with the different mappings. Discrete Wigner functions are also calculated. © 1995.